Translation of English Idioms in Novel The Lion the Witch and The Wardrobe and Its Translation - Sekarsari, Armita Ayu (Prosiding University Research Colloquium, 2021)
This research examines the English idioms found in the novel The Lion the Witch and The Wardrobe and their translation. The aim is to classify the kinds of idiomatic expression and their Indonesian translation. This research uses descriptive-qualitative method. Data are the sentences which contain English idioms and their translation. Data sources are the novel The Lion, the Witch, and The Wardrobe and its Indonesian translation (Sang Singa, Sang Penyihir dan Lemari) limited from chapter one to six. The technique of collecting data was documentation. The technique of analysis data used comparison method. The result shows that the types of idiom found in this novel namely irregular form clear meaning, regular form unclear meaning, and irregular form unclear meaning and they are translated accurately in Indonesian in the same types of idiom. From 35 analyzed data source of chapter one until chapter six in the novel contain idiom, 54,29% data belong to the first type, 37,14% data belong to the second type, and 8,57% data belong to the third type of idiom. The research results can be applied in teaching learning of translation subject